Information Management Behaviour of Fishermen of Coastal Districts of Tamilnadu in Relation to Communication Technologies - A Comparative Study - Arul Oli, G., Santhakumar, R., Veerabhadran, K., Neethiselvan, N and P. Jawahar, (Indian Journal of Extension Education, 2023)
The present comparative research was undertaken to study the different dimensions of Information Management Behaviour (IMB) of fishermen of districts of Tamil Nadu. A total of 400 respondents were selected using simple random sampling from four coastal districts of Tamilnadu. There were two districts (Pudukottai and Thoothukudi) taken as control area and two districts were taken as ICTs impact study area (Nagapattinam and Kanyakumari). The results revealed that more than one-half (56.00%) of the fishermen in the control area had the low level of IMB followed by medium (29.00%) and high (15.00%) level. Whereas in ICT impact area, the majority (57.00%) of the fishermen belonged to the high level of IMB category followed by medium (28.00%) and low (15.00%) level. The R2 value can predict IMB of fishermen for control and ICT impact area with 65.00% and 74.10% accuracy respectively. The significance value of the paired t-test ð=0.019 (t5=7.060, p=0.019) confirmed statistically that there is significance between the sample means of control and ICT impact area on dimensions of IMB of fishermen.